HUBUNGAN SKOR INDEKS MASSA TUBUH TERHADAP TEKANAN DARAH SISTOLIK DAN SKOR KUALITAS HIDUP LANSIA DI KECAMATAN LOWOKWARU - Wilujeng, Catur Saptaning; Habibie, Intan Yusuf; Ventiyaningsih, Agustiana Dwi Indiah; Maulidiana, Annisa Rizky; Kinasih, Adiandari Astu; Cedarta, Marchya Karima; Kharisma, Merinda Yolla; Fitri, Annisa; Putri, Ristavia (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
Indonesia's population structure is starting to enter an aging population, characterized by the percentage of the elderly population from 2020 which is expected to reach more than 10 percent. In fact, from BPS projections, in 2045 Indonesia's elderly are estimated to reach almost one-fifth of Indonesia's entire population (BPS, 2020). Older people will experience a decrease in the function of several body organs which can cause decreased absorption of nutrients. This situation will of course affect the nutritional status of the elderly themselves, both undernutrition and overweight (overweight and obesity). Apart from that, it is necessary to pay attention to health problems which are currently a health problem often experienced by the elderly, namely hypertension. This research is an analytical observational study with a cross sectional approach. The research sample was taken using a purposive sampling method with a minimum sample size of 100 elderly people. Nutritional status data was obtained by anthropometric measurements, blood pressure data was obtained by measuring the blood pressure of the elderly, and quality of life data was obtained by interviewing the WHOQOL BREF questionnaire. The results of the study showed that there was a significant relationship between Body Mass Index (BMI) and systolic blood pressure in the elderly (p=0.035, r=0.211) and there was a relationship between Body Mass Index (BMI) and the quality of life score in the elderly (p=0.034, r=0.212 ). The conclusion of this research is that the greater the body mass index (BMI) score of an elderly person, the higher the systolic blood pressure and the higher the quality of life score of an elderly person. Keyword: elderly, systolic blood pressure, quality of life, body mass index